Avaliação da funcionalidade e mobilidade em pessoas idosas da Universidade da Maturidade em Tocantinópolis, TO. - Silva, Miguel Otávio Pires (Universidade Federal do Tocantins, 2024)
The objective of this work was to evaluate and compare the functionality and mobility of elderly people at the Universidade da Maturidade in Tocantinópolis, TO. This is a cross-sectional study with a quantitative approach carried out with elderly people from the University of Maturity (UMA) in the Tocantinópolis, TO center. Sociodemographic and anthropometric information was collected, in addition to the following questionnaires: Mini Mental State Examination, Katz Index, Lawton and Brody Scale and the TUG test (Timed Up and Go Test) was applied. Data analysis was carried out using descriptive and inferential statistics. Participants were divided into two groups: group I (without functional dependence) and group II (with functional dependence), according to the Katz Index, which assessed the degree of dependence in relation to basic activities of daily living (BADL). 40 elderly people participated in this research, with group 1 having 29 participants (55% were women), average age of 69.45 years (±7.30), predominance of the age group of 60 to 69 years (58.6%) . Group II, 11 participants (54.5% women), mean age 76.09 (±5.54), age range 70-79 (years) (54.5%), elderly people aged 80 or over corresponded to by 36.4%. The difference between the average age (p=0.005) and in relation to the age group (p=0.008) of the two groups was statistically significant. In relation to BADL, 72.5% of the elderly are independent and 27.5% are dependent. There was a significant difference in relation to the degree of dependence on Instrumental Activities of Daily Living (IADL) (p=0.02) and in the degree of functional mobility (p=0.02) according to the degree of dependence on BADL in relation to the averages of TUG between the two groups, a significant difference was observed (p=0.025). In the group without dependence, an average of 8.24 (± 2.71) was obtained and in the group with dependence, an average of 11.03 (±3.23). The majority of participants were assessed as independent in carrying out basic activities of daily living, however a significant number of dependent individuals require assistance from the UMA interdisciplinary team, minimizing the postponement of functional incapacity. It was found that independent elderly people performed better on the TUG test than those who were dependent. Therefore, it is important to encourage the planning of actions and educational strategies for the health of older people with a holistic approach, contributing to the adoption of healthy habits, improving quality of life and promoting healthy aging.